Effects of health education based on the theory of knowledge-attitude-practice on mental health and quality of life in patients with newly diagnosed primary liver cancer (基于知信行理论的健康教育对首诊原发性肝癌患者心理状态及生活质量的影响) - HE Cuijuan (何翠娟); WANG Jie (汪婕); ZHU Hengmei (朱恒美); YANG Yuan (杨远) (中西医结合护理)
Objective To observe the effect of health education based on the theory of knowledge-attitude-practice(KAP)on mental health and quality of life in patients with newly diagnosed primary liver cancer. Methods Totally80 patients with primary liver cancer were selected as the study object, and 80 patients were randomly divided into control group (n=40) and the observation group (n=40). All patients received routine care and health guidance during the treatment, and patients in the observation group received KAP-based health education. A self-designed questionnaire was used to evaluate the patients’ knowledge, attitude and practice about disease. Self-rating Depression Scale (SDS) and Self-rating Anxiety Scale (SAS) were used to measure the psychological status of patients. The World Health Organization Quality of Life assessment (WHOQOL-BREF) was used to assess the patient quality of life. Results Dimensional scores of knowledge, attitude and practice in the observation group were higher than those in the control group after intervention( P＜0. 01). The SAS and SDS scores in the observation group were lower than those in the control group after intervention( P＜0. 01). Scores of physical, psychological and social dimension in the observation group were higher than those in the control group after intervention( P＜0. 01). Conclusion KAP-based health education can effectively improve the mental health and quality of life of patients with newly diagnosed primary liver cancer. (目的 观察基于知信行理论的健康教育对首次诊疗原发性肝癌患者心理状态及生活质量的影响。方法 选取2022年5月—2023年5月在医院首次就诊治疗的原发性肝癌患者80例为研究对象, 随机分为对照组(n=40)和观察组(n=40)。治疗期间, 对照组接受常规护理和健康教育指导, 观察组在对照组基础上联合知信行健康教育。采用自制问卷调查患者疾病知信行水平, 采用抑郁自评量表(SDS)和焦虑自评量表(SAS)评估患者心理状态, 采用世界卫生组织生存质量测定量表( WHOQOL -BREF) 评价患者生存质量。结果 干预后, 观察组知信行问卷量表知识、态度和行为评分均高于对照组, 差异有统计学意义(P＜0. 01)。干预后, 研究组患者SAS、SDS评分均低于对照组, 差异有统计学意义(P＜0. 01)。干预后, 观察组患者WHOQOL－BREF量表生理、心理和社会关系维度者评分均高于对照组, 差异有统计学意义(P＜0. 01)。结论 基于知信行理论的健康教育能有效改善首诊原发性肝癌的心理状态, 提高生活质量。)